2020
DOI: 10.1155/2020/8425912
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Anthropometric Measurements for Identifying Diabetes and Prediabetes among Civil Servants in a Regional City of Northern Ethiopia: A Cross-Sectional Study

Abstract: Back ground. Diabetes mellitus is an emerging noncommunicable disease in Ethiopia. Overlooking an appropriate tool for identifying diabetes and prediabetes would have significant impact for future diabetes and prediabetes projections and its management. Therefore, the study aims to examine the effectiveness of anthropometric measurements for identifying prediabetes and diabetes in Mekelle city, Tigray, Northern Ethiopia. Methods. The study involved a cross-sectional survey carried out from October 2015 to Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
(38 reference statements)
4
11
1
Order By: Relevance
“…Further, WC and WHtR had a better discriminatory ability for T2D than BMI. This agrees with other findings from Guinea, Kenya, Cameroon, and Ethiopia which have shown that WC is a better predictor of T2D (7,(9)(10)(11)(12). Globally, these findings are consistent with a meta-analysis that found that WC and WHtR had better discrimination for T2D than BMI (6).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Further, WC and WHtR had a better discriminatory ability for T2D than BMI. This agrees with other findings from Guinea, Kenya, Cameroon, and Ethiopia which have shown that WC is a better predictor of T2D (7,(9)(10)(11)(12). Globally, these findings are consistent with a meta-analysis that found that WC and WHtR had better discrimination for T2D than BMI (6).…”
Section: Discussionsupporting
confidence: 92%
“…The optimal BMI cut-off was 27.1 kg.m -2 and 24.8 kg.m -2 in women and men, respectively. These findings were consistent with a Ghanaian study which found an overweight BMI of 26.2 kg.m -2 as the optimal cut-off in women ( 8) and an Ethiopian study that reported a normal weight BMI of 23.0 kg.m -2 as the optimal cut-off in men (12). Also, this is in agreement with increasing evidence that Africans develop T2D at a lower BMI (23) than the current obesity cut-off of 30kg.m -2 (24).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations